Sacraments that Forgive Sins - Janczewski, Zbigniew (Prawo Kanoniczne, 2025)
The forgiveness of sins takes place not only in the sacrament of penance and reconciliation but also in baptism and the anointing of the sick. This article outlines the issue of sacramental forgiveness of sins, taking into account the concept and types of sin, as well as the Church’s doctrine on these matters. It also examines Church documents concerning the ministers empowered to forgive sins in these sacraments, the matter and form of the sacraments, and the conditions required of those receiving baptism, penance, and the anointing of the sick.